2014
DOI: 10.1155/2014/351598
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 Supplementation Improves Oxidative Stress and Enhances Serum Paraoxonase/Arylesterase Activities in Streptozotocin-Induced Diabetic Rats

Abstract: The purpose of this study was to investigate the effects of vitamin B6 (Vit B6) on oxidant and antioxidant status in streptozotocin-induced diabetic rats. Thirty-two Wistar rats were divided into four groups: control (C), control + Vit B6 group (C + Vit B6), diabetes (D), and diabetes + Vit B6 group (D + Vit B6). Vit B6 (4 mg/kg body weight) was administered in drinking water for 4 weeks after the induction of diabetes. Vitamin B6 reduced serum total cholesterol level in the C + Vit B6 (P < 0.01) and D + Vit B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 49 publications
(53 reference statements)
2
16
1
Order By: Relevance
“…In fact, many previous studies suggested that PON and ARE activities can reduce diabetes mellitus complications [20,47,52]. However, other studies indicated that the inactivation of antioxidant enzymes such as PON1 might be prevented by the addition of antioxidant vitamins or herbal supplements [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many previous studies suggested that PON and ARE activities can reduce diabetes mellitus complications [20,47,52]. However, other studies indicated that the inactivation of antioxidant enzymes such as PON1 might be prevented by the addition of antioxidant vitamins or herbal supplements [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, vitamin B 6 supplementation had no effect on hepatic GSH levels in control rats, with or without supplementation [135], nor did it alter GPx levels in homocysteinemic rats [133]. Unexpectedly, vitamin B 6 supplementation increased blood GPx levels of control rats, indicating that the vitamin may directly stimulate the GSH redox system under normal conditions [138].…”
Section: Effects Of Micronutrient Supplementationmentioning
confidence: 99%
“…However, to prevent tissue damage caused by oxidative stress, the major antioxidant enzymes such as superoxide dismutases (SOD) and glutathione peroxidase (GSH-PX) played an important role in maintaining the balance between antioxidants and oxidation in vivo [ 17 27 ]. Tas et al [ 31 ] reported that increased activities of SOD and GSH-PX could reduce the oxidative damage induced by reactive oxygen species (ROS) in rats.…”
Section: Introductionmentioning
confidence: 99%